2005
DOI: 10.1248/bpb.28.1702
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Theanine on Alcohol Metabolism and Hepatic Toxicity

Abstract: Theanine (Fig. 1), a major amino acid in green tea, is a umami (the fifth taste sensation)-component of tea and is contained 2-3% in tea leaves.1,2) Theanine is a glutamate derivative and is used extensively as supplements and beverages, because it has a brain nerve function such as a relaxing effect due to inducing alpha waves. [3][4][5][6] But there are few reports about pharmacological action of theanine in comparison with catechin or caffeine, major tea components, and its effects on living individuals hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…One possible mechanism by which EGCG prevents ethanol-induced hepatotoxicity is inhibition of the catalytic activity of CYP2E1, similarly to theanine (the predominant amino acid in green tea), 52) but JimenezLopez et al found that EGCG does not affect CYP2E1-mediated ethanol metabolism in the human hepatoma HepG2 cell line, which constitutively expresses human CYP2E1. 53) Similarly, we found in this study that dietary EGCG had no effect on CYP2E1 expression in ethanol-administered rats.…”
Section: Discussionmentioning
confidence: 99%
“…One possible mechanism by which EGCG prevents ethanol-induced hepatotoxicity is inhibition of the catalytic activity of CYP2E1, similarly to theanine (the predominant amino acid in green tea), 52) but JimenezLopez et al found that EGCG does not affect CYP2E1-mediated ethanol metabolism in the human hepatoma HepG2 cell line, which constitutively expresses human CYP2E1. 53) Similarly, we found in this study that dietary EGCG had no effect on CYP2E1 expression in ethanol-administered rats.…”
Section: Discussionmentioning
confidence: 99%
“…ferent inducers in different organs (Hong et al, 2001;Das et al, 2002;Hiroyasu et al, 2002;Skrzydlewska et al, 2002;Zhang et al, 2002;Chen et al et al, 2004;Augustyniak et al, 2005;El-Beshbishy, 2005;Erba et al, 2005;Mohamadin et al, 2005;Sadzuka et al, 2005;Skrzydlewska et al, 2005;Yamamoto et al, 2006). Green tea suppresses reactive oxygen species (ROS) formation through polyhydroxy phenolics such as catechins that impart strong antioxidant activity.…”
Section: Figmentioning
confidence: 99%
“…Recent studies have reported that theanine has various favorable physiological functions including neuroprotection in transient ischemic neuronal death (Kakuda et al 2000;Yamada et al 2005), relaxing effects under resting conditions (Abdou et al 2006;Lu et al 2004), hypolipidemic functions (Chiang et al 2005), regulation of systemic blood pressure (Yokogoshi et al 1995), suppression of the stimulatory action of caffeine (Nozawa et al 2000), modulation of neurotransmitter (Yamada et al 2009), and protection against hepatic toxicity (Sadzuka et al 2005). Additionally, studies on test rats have shown that repeated, extremely high doses of theanine cause little to no harmful psychological or physical effects (Borzelleca et al 2006).…”
Section: Introductionmentioning
confidence: 99%